2014
DOI: 10.3109/00365521.2014.936032
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of single-user peroral cholangioscopy in sclerosing cholangitis

Abstract: SOC is equally accurate in cancer diagnosis in sclerosing cholangitis and patients with single biliary strictures. However, cholangioscope insertion may be hampered by bile duct narrowing and post-SOC cholangitis is more common in sclerosing cholangitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Similarly, high rates of stone clearance have been reported for direct cholangioscopy, albeit in smaller studies 113. Cholangioscopy is safe but cholangitis has been reported to occur in up to 9% of patients,112 necessitating the use of prophylactic antibiotics. Otherwise complications are comparable to conventional ERCP 114.…”
Section: Endoscopic Management Of Cbdsmentioning
confidence: 93%
“…Similarly, high rates of stone clearance have been reported for direct cholangioscopy, albeit in smaller studies 113. Cholangioscopy is safe but cholangitis has been reported to occur in up to 9% of patients,112 necessitating the use of prophylactic antibiotics. Otherwise complications are comparable to conventional ERCP 114.…”
Section: Endoscopic Management Of Cbdsmentioning
confidence: 93%
“…However, transpapillary cholangioscopy may increase the ability to distinguish between malignant and benign bile duct stenoses in patients with PSC through targeted-biopsies [16] and may be considered in unclear cases. Cholangioscopy seems equally accurate in cancer diagnosis in sclerosing cholangitis (PSC and IgG4-related sclerosing cholangitis) compared to patients with single bile duct strictures [18]. In this retrospective multi-centre caseecontrol study, cholangioscopy showed similar sensitivity, specificity, and accuracy for cancer diagnosis [18].…”
Section: Cholangioscopymentioning
confidence: 69%
“…Cholangioscopy seems equally accurate in cancer diagnosis in sclerosing cholangitis (PSC and IgG4-related sclerosing cholangitis) compared to patients with single bile duct strictures [18]. In this retrospective multi-centre caseecontrol study, cholangioscopy showed similar sensitivity, specificity, and accuracy for cancer diagnosis [18]. However, the insertion of the cholangioscope is technically challenging and may be complicated or even impossible by tight distal strictures and post-procedural cholangitis is more frequent in patients with sclerosing cholangitis [18].…”
Section: Cholangioscopymentioning
confidence: 75%
See 1 more Smart Citation
“…This technique has high sensitivity and specificity for the diagnosis of biliary strictures [30]. A study by Fukuda et al [31] showed that the sensitivity of combined ERCP/oral cholangioscopy in diagnosing biliary lesions was 93% compared with only 58% for ERCP alone [32].…”
Section: Discussionmentioning
confidence: 99%